The Right to Vote for People Who Experience Mental/Memory Disorders in Elections Post Constitutional Court Ruling No.135/PUU-XIII/2015 - Shobahah, Nurush (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
ABSTRACT: MK Decision No.135/PUU-XIII/2015 stipulates that to declare that a voter with mental/memory disorders does not meet the requirements, they must use a mental illness certificate from a doctor. Voters with cognitive/memory disorders who do not have a medical certificate from a doctor will still be recorded in the Permanent Voter List or DPT data collection. Problems arise about how to update the data. What problems arise? Are there voters with mental/memory disorders exercising their right to vote? In reality, many voters with cognitive/memory disorders do not have a cognitive/memory disorder certificate from a doctor. Election organizers responded by continuing to register and include them in the DPT regardless of whether they could exercise their right to vote. The reason is that election organizers avoid the potential for criminal acts to eliminate someone's right to vote. Due to this situation, researchers feel that there is a need to update and reconstruct the voter list updating system for voters with mental/memory disorders. The system used is the Civil Registry, so the government bears data availability for updating. This research is included in socio-legal research with two approaches: the statutory approach and the case approach. The study was conducted in Tulungagung Regency. Keywords: Election, Voters with Mental/Memory Disorders, DPT